Chemistry and Biology of Teixobactin. Issue 21 (12th December 2017) - Guo, Chuchu; Mandalapu, Dhanaraju; Ji, Xinjian; Gao, Jiangtao; Zhang, Qi
Abstract: Bacterial resistance to existing drugs is becoming a serious public health issue, urging extensive search for new antibiotics. Teixobactin, a cyclic depsipeptide discovered in a screen of uncultured bacteria, shows potent activity against all the tested Gram‐positive bacteria. Remarkably, no teixobactin‐resistant bacterial strain has been obtained despite extensive efforts, highlighting the great potential of teixobactin as a lead compound in the fight against antimicrobial resistance (AMR). This review summarizes recent progresses in the understanding of many aspects of teixobactin, including chemical structure, biological activity, biosynthetic pathway, and mode of action. We also discuss the different synthetic strategies in producing teixobactin and its analogues, and the structure–activity relationship (SAR) studies. Abstract : Teixobactin is a cyclic depsipeptide exhibiting potent activity against all the tested Gram‐positive bacteria. Remarkably, thus far no teixobactin‐resistant bacterial strain has been obtained despite extensive efforts. This Review discusses recent progress in the understanding of many aspects of teixobactin, including biological activity, biosynthetic pathway, mode of action, and the structure–activity relationship studies.